2017
DOI: 10.3847/1538-4357/aa898f
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Core Mass Function (CMF) from Filaments: Under Which Circumstances Can Filament Fragmentation Reproduce the CMF?

Abstract: Observations suggest that star formation in filamentary molecular clouds occurs in a two-step process, with the formation of filaments preceding that of prestellar cores and stars. Here, we apply the gravo-turbulent fragmentation theory of Hennebelle & Chabrier (2008, 2009, 2013 to a filamentary environment, taking into account magnetic support. We discuss the induced geometrical effect on the cores, with a transition from 3D geometry at small scales to 1D at large ones. The model predicts the fragmentation be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 103 publications
2
25
0
Order By: Relevance
“…This could suggest, however, that coherent density-driven filaments originate from shocks directly associated with compressive turbulence. Our results are in agreement with the gravoturbulent models of Larson (1981), Hennebelle & Chabrier (2008), and more recently Lee et al (2017) which take into account the scale dependance of the supporting thermal, turbulent, and magnetic energies. The magnetic field certainly also plays a role in the formation of large filaments, where it has been found oriented perpendicularly to nearby filaments, such as Musca and Taurus (Palmeirim et al 2013;Planck Collaboration XXXIII 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This could suggest, however, that coherent density-driven filaments originate from shocks directly associated with compressive turbulence. Our results are in agreement with the gravoturbulent models of Larson (1981), Hennebelle & Chabrier (2008), and more recently Lee et al (2017) which take into account the scale dependance of the supporting thermal, turbulent, and magnetic energies. The magnetic field certainly also plays a role in the formation of large filaments, where it has been found oriented perpendicularly to nearby filaments, such as Musca and Taurus (Palmeirim et al 2013;Planck Collaboration XXXIII 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, as stressed in Paper I, the high-mass part of the mass spectra tends to present a power law that is too shallow compared to the canonical Salpeter distribution. If dense clusters turn out to be assembled from material where cores are already developed, the preexisting cores may play a stronger role and the peak of the IMF could be inherited from the peak of the core mass function (CMF), as proposed theoretically in Padoan et al (1997), Hennebelle & Chabrier (2009), Hennebelle (2012), Hopkins (2012), Lee & Hennebelle (2016a), and Lee et al (2017), and suggested by simulations (Gong & Ostriker 2015;Hennebelle 2018). This picture is suggested by the observations of the CMF, which resembles the IMF (Motte et al 1998;Alves et al 2007;AndrĂ© et al 2010;Könyves et al 2015), and it could be the dominant mode in some environments.…”
Section: What Sets the Peak Of The Imf: Is There A Cosmic Conspiracy?mentioning
confidence: 99%
“…The fragmentation of purely thermal, equilibrium filaments may be expected to result in a narrow ("ÎŽ-like") prestellar CMF sharply peaked at the median thermal Jeans mass (see Lee et al 2017). However, at least two effects contribute to broadening the observed CMF.…”
Section: The Role Of Filaments In the Prestellar Cmfmentioning
confidence: 99%